2019
DOI: 10.1108/md-08-2017-0784
|View full text |Cite
|
Sign up to set email alerts
|

Marketing innovation and sustainable competitive advantage of manufacturing SMEs in Ghana

Abstract: Purpose The purpose of this paper is to establish how small- and medium-sized enterprises (SMEs) in water, beverage, soap, detergent, metal fabrication, wood and furniture manufacturing industries can sustain or improve their competitive advantage by integrating specific resources and capabilities. The paper seeks to offer an alternative framework “resource capability-based view (RCBV)” that provides a strategic marketing direction for SMEs regarding how innovative marketing practices and dynamic marketing cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(150 citation statements)
references
References 56 publications
6
133
0
11
Order By: Relevance
“…The marketing innovation variable has a positive and significant effect on marketing performance. This is in accordance with the research by Quaye and Mensah (2018) and Guzman et al, (2018). The descriptive analysis results in this study indicate that different pricing methods from competitors can result in higher sales average.…”
Section: B Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The marketing innovation variable has a positive and significant effect on marketing performance. This is in accordance with the research by Quaye and Mensah (2018) and Guzman et al, (2018). The descriptive analysis results in this study indicate that different pricing methods from competitors can result in higher sales average.…”
Section: B Discussionsupporting
confidence: 94%
“…If the firm is in a tight industrial competition, immediate innovation is recommended to continue to compete with its competitors. In another study, Quaye and Mensah (2018) found that marketing innovation through price and promotion can have an impact on marketing performance. Results from a study by Quareshiet et al (2017) indicated that promotional innovations have a positive effect on marketing performance.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In order for a family business to have a chance at successful transfer to successor generations, it must monitor, evaluate, and actively implement modern marketing tools. This reality has been validated by Quaye and Mensah (2019). According to their research companies must integrate specifi c resources and capabilities, apply innovative marketing processes with the option for dynamic marketing, and thereby create sustainable market value.…”
Section: Family Businessesmentioning
confidence: 99%
“…No obstante, los investigadores están descuidando las innovaciones organizativas o en marketing, que son a la par fundamentales para el crecimiento, rendimiento y funcionamiento efectivo (Abdul, Kuhn y Ahmed, 2018;Chung y Kim, 2017;Damanpour, 1991;Damanpour y Evan, 1984). Actualmente, son escasos los estudios sobre las innovaciones enfocadas al marketing (Gunday, Ulusoy, Kilic y Alpkan, 2011;Quaye y Mensah, 2019;Reiner, Reimann y Vitkauskaite, 2016;Zakerian et al, 2017), a pesar de que la innovación en marke-ting como estrategia empresarial permite a las organizacio-nes establecer una relación más estrecha con sus clientes hasta convertirlos en promotores de la propia empresa (Kotler y Keller, 2006). Ante tal situación, es importante la realización de estudios acerca de la innovación enfocada al marketing, principalmente en organizaciones distintas a las de servicios (Contò, Fiore, Vrontis y Silvestri, 2015;Geldes y Felzensztein, 2013;Heredia, Geldes, Kunc y Flores, 2019;Quaye y Mensah, 2019).…”
Section: Introductionunclassified
“…Actualmente, son escasos los estudios sobre las innovaciones enfocadas al marketing (Gunday, Ulusoy, Kilic y Alpkan, 2011;Quaye y Mensah, 2019;Reiner, Reimann y Vitkauskaite, 2016;Zakerian et al, 2017), a pesar de que la innovación en marke-ting como estrategia empresarial permite a las organizacio-nes establecer una relación más estrecha con sus clientes hasta convertirlos en promotores de la propia empresa (Kotler y Keller, 2006). Ante tal situación, es importante la realización de estudios acerca de la innovación enfocada al marketing, principalmente en organizaciones distintas a las de servicios (Contò, Fiore, Vrontis y Silvestri, 2015;Geldes y Felzensztein, 2013;Heredia, Geldes, Kunc y Flores, 2019;Quaye y Mensah, 2019). Además, según la Organización para la Cooperación y el Desarrollo Económicos (OECD, 2005), la innovación en marketing permite a las empresas "satisfacer mejor las necesidades de los consumidores, abrir nuevos mercados o posicionar en el mercado sus productos de una nueva manera con el fin de aumentar sus ventas" (p. 60).…”
Section: Introductionunclassified